PKM Transformasi Koperasi Siswa melalui Pendampingan Digitalisasi pada Pengelola Koperasi di Madrasah Ibtidaiyah se Kota Batu - Waluyo Satrio Adji; Yulia Eka Putrie; Ahsin Dinal Mustofa (Universitas Nurul Jadid, 2023)
Conventional management raises technical problems that have a big impact on managing cooperatives. The aim of this service is to provide planning, action, observation and reflection on the transformation of student cooperatives through digitalization assistance to cooperative managers in madrasah ibtidaiyah throughout Batu City. The method used in service is PAR-based, described in a cycle consisting of planning, action, observation and reflection. The results of the service were obtained from (1) Activities at this planning stage, namely the preparation of training activity materials. This activity was carried out in the form of a focus group discussion (FGD) involving the chairman of the Batu City KKMI, researchers and resource persons. The agreed FGD results. (2) The action stage is actualized with the facilities of the research team. The training will be carried out offline on 11 and 12 July 2023. (3) Observations were carried out to understand the successes and weaknesses of school cooperative digitalization training. The results of observations carried out during the training revealed weaknesses and strengths experienced by researchers, coordinators and teachers both in terms of attitudes and obstacles in training such as facilities and infrastructure. (4) Training activities can be reflected on and evaluated. Evaluation activities were carried out in the field on August 18 2023 at Madrasah Ibtidaiyah in Batu City. Reflection and evaluation in the form of conveying supporting and inhibiting factors during training activities and appreciation to participants..